Applicability and academic formation of integrative and complementary practices: A critical assessment of professors and students in the health field (Research, Society and Development, 2024)
Objective: To evaluate the opinions of professors and students in the health field at a university regarding Integrative and Complementary Practices (ICPs). Methodology: A questionnaire was administered to assess the epidemiology, knowledge, and opinions on the effectiveness, relevance, and applicability of ICPs. Results: The majority had prior contact with ICPs (p